Lagrangian photochemical modeling studies of the 1987 Antarctic spring vortex. I - Comparison with AAOE observations - Jones, R. L.; Austin, J.; Mckenna, D. S.; Anderson, J. G.; Fahey, D. W.; Farmer, C. B.; Vedder, J. F. (1989)
Results from the Lagrangian photochemical model integrated along computed air parcel trajectories intersected by the ER-2 aircraft are presented and compared with AAOE observations. According to the model, the BrO observations made from the ER-2 within the dehydrated denitrified region are consistent with there being approximately 5 parts per trillion by volume of BrO(y) at 428 K in spring. Within the high ClO region, ozone destruction rates are expected to exceed 2 percent/d with approximately 80 percent due to the ClO dimer mechanism.